Solve for x (complex solution)
x=-10+i\times 2\sqrt{55}\approx -10+14.832396974i
x=-i\times 2\sqrt{55}-10\approx -10-14.832396974i
Graph
Share
Copied to clipboard
0.25x^{2}+5x+80=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-5±\sqrt{5^{2}-4\times 0.25\times 80}}{2\times 0.25}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 0.25 for a, 5 for b, and 80 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-5±\sqrt{25-4\times 0.25\times 80}}{2\times 0.25}
Square 5.
x=\frac{-5±\sqrt{25-80}}{2\times 0.25}
Multiply -4 times 0.25.
x=\frac{-5±\sqrt{-55}}{2\times 0.25}
Add 25 to -80.
x=\frac{-5±\sqrt{55}i}{2\times 0.25}
Take the square root of -55.
x=\frac{-5±\sqrt{55}i}{0.5}
Multiply 2 times 0.25.
x=\frac{-5+\sqrt{55}i}{0.5}
Now solve the equation x=\frac{-5±\sqrt{55}i}{0.5} when ± is plus. Add -5 to i\sqrt{55}.
x=-10+2\sqrt{55}i
Divide -5+i\sqrt{55} by 0.5 by multiplying -5+i\sqrt{55} by the reciprocal of 0.5.
x=\frac{-\sqrt{55}i-5}{0.5}
Now solve the equation x=\frac{-5±\sqrt{55}i}{0.5} when ± is minus. Subtract i\sqrt{55} from -5.
x=-2\sqrt{55}i-10
Divide -5-i\sqrt{55} by 0.5 by multiplying -5-i\sqrt{55} by the reciprocal of 0.5.
x=-10+2\sqrt{55}i x=-2\sqrt{55}i-10
The equation is now solved.
0.25x^{2}+5x+80=0
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
0.25x^{2}+5x+80-80=-80
Subtract 80 from both sides of the equation.
0.25x^{2}+5x=-80
Subtracting 80 from itself leaves 0.
\frac{0.25x^{2}+5x}{0.25}=-\frac{80}{0.25}
Multiply both sides by 4.
x^{2}+\frac{5}{0.25}x=-\frac{80}{0.25}
Dividing by 0.25 undoes the multiplication by 0.25.
x^{2}+20x=-\frac{80}{0.25}
Divide 5 by 0.25 by multiplying 5 by the reciprocal of 0.25.
x^{2}+20x=-320
Divide -80 by 0.25 by multiplying -80 by the reciprocal of 0.25.
x^{2}+20x+10^{2}=-320+10^{2}
Divide 20, the coefficient of the x term, by 2 to get 10. Then add the square of 10 to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+20x+100=-320+100
Square 10.
x^{2}+20x+100=-220
Add -320 to 100.
\left(x+10\right)^{2}=-220
Factor x^{2}+20x+100. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x+10\right)^{2}}=\sqrt{-220}
Take the square root of both sides of the equation.
x+10=2\sqrt{55}i x+10=-2\sqrt{55}i
Simplify.
x=-10+2\sqrt{55}i x=-2\sqrt{55}i-10
Subtract 10 from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}